A Comparative Analysis of Mental Toughness Among All India Inter-University Men’s Pencak Silat Athletes Across Universities - Jose, Mary Suraj; Mukkadan, Priyanka Gupta (Journal of Educational Research and Policies, 2026)
This study examines the mental toughness of athletes from four universities participating in the All India Inter - University Men’s Pencak Silat Team. Mental toughness is a critical psychological trait that influences an athlete’s ability to perform under pressure, remain focused, and recover after setbacks. A validated Mental Toughness Questionnaire (Goldberg, 1998) was administered to 80 athletes from Bengaluru North University, Bangalore University, Guru Nanak Dev University, and Chandigarh University. The results revealed no statistically significant differences in mental toughness scores between the universities. However, descriptive trends suggested slightly higher overall mental toughness scores among athletes from Bengaluru North University. These findings highlight the importance of personalized mental toughness training strategies, regardless of university affiliation.